Theoretical Model of Time–Temperature Superposition Principle of the Self‐Healing Kinetics of Supramolecular Polymer Nanocomposites. Issue 20 (3rd August 2018) - Zheng, Zijian; Xia, Xiuyang; Zeng, Xianxiang; Li, Xiu; Wu, Youping; Liu, Jun; Zhang, Liqun
Abstract: The matrix‐free polymer nanocomposites (PNCs) formed by polymer‐grafted nanoparticles(NPs) gain enormous attention due to their controllable morphology and robust properties. Herein, through molecular dynamics simulation, such PNCs are successfully constructed, and the dispersion state of the NPs can be tailored by varying the grafting density. By manipulating the interaction strength between the end groups of the grafted polymer chains, the tensile fracture behavior and the chain orientation are examined. It is revealed that both of them fall down at large strain because of the propagation of the cavities. By probing the self‐healing kinetics at various self‐healing temperature and time, a time−temperature superposition principle, similar to the Williams, Landel and Ferry equation, is proposed. These results could provide some fundamental guidelines for the design and fabrication of high performance PNCs with excellent self‐healing functionality. Abstract : The structure manipulation as well as the self‐healing capability of the matrix‐free polymer nanocomposites from polymer‐grafted nanoparticles are studied through molecular dynamics simulation.